The Moderating Role of CEO Characteristics in the Relationship between Financial Conditions and Corporate Debt Policy - Heriyanto Heriyanto; Novita Febriany; Mischella Engel (Journal of Enterprise and Development (JED), 2025)
Purpose: This study investigates the influence of firm financial characteristics—reflecting asymmetric information—on corporate debt policy, while also examining the moderating role of CEO characteristics within the framework of upper echelon theory.Method: The sample consists of 60 non-financial firms listed on the Indonesia Stock Exchange (IDX) during 2013–2022, selected through purposive sampling. Panel data regression analysis with moderating variables was employed to assess how CEO characteristics interact with internal financial indicators.Result: Results show that liquidity (current ratio) and profitability (return on equity) have a significant negative effect on companies’ debt-to-equity ratio, indicating that more liquid and profitable firms rely less on external debt. Tangible assets do not significantly influence debt-to-equity ratio. Among CEO characteristics, only tenure significantly moderates the relationship between profitability and debt-to-equity ratio, highlighting the strategic role of experienced CEOs in financing decisions.Practical Implications for Economic Growth and Development: The findings suggest that capital structure decisions are shaped jointly by internal financial conditions and leadership traits. Firms with stable financial profiles, guided by experienced CEOs, are more likely to establish optimal debt policies, enhancing resilience during economic shocks, safeguarding employment, and improving competitiveness—ultimately supporting broader economic growth.Originality/Value: This study contributes by integrating asymmetric information theory and upper echelon theory into a unified analytical model. By revealing how CEO characteristics moderate the impact of financial conditions on debt policy, it offers deeper insight into the complex dynamics of strategic financing decisions.